Baseline study of the quality of life of land reform beneficiaries in Limpopo Province : a case study of Gertrudsburg - Makhura, M.T. (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Land Development))--University of Pretoria, 2007.